Acute Coronary Syndrome in Acute Myeloid Leukemia with Maturation Accompanying Megakaryocytic Differentiation - Kentaro Odani; Junya Abe; Yoshiaki Tsuyuki; Soshi Yanagita; Kazuya Shiogama; Mitsuhiro Tachibana; Yutaka Tsutsumi (Hindawi Limited, 2020)
An autopsy case (85-year-old Japanese male) of myeloperoxidase- (MPO-) positive acute myeloid leukemia with maturation (M1) accompanying megakaryocytic differentiation is presented. The patient manifested acute coronary syndrome. Even after emergent percutaneous coronary intervention, his performance status remained poor, so no chemotherapy against leukemia was given. The final white blood cell count reached 291,700/μL, and the platelet count was elevated to 510,000/μL. No cytogenetic studies were performed. He died at the 25th day of hospitalization. Autopsy revealed marked leukemic infiltration to the endocardium and subendocardial myocardium. Subendocardial myonecrosis was surrounded or replaced by the leukemic blasts, and neither granulation tissue reaction nor fibrosis was observed. In the cardiovascular lumen, lard-like blood clots were formed and microscopically consisted of leukemic blasts and platelets (leukemic thrombi). Infiltration of leukemic blasts was seen in the body cavities and systemic organs including the lung. The MPO-positive blasts lacked azurophilic granules and expressed the stem cell markers, CD34 and CD117 (c-kit). No features of myelofibrosis were seen in the 100% cellular marrow. In the endocardium, liver, lymph nodes, and bone marrow, megakaryocytic cells (CD42b/CD61+, MPO-) were distributed, while the small-sized blastic cells in the blood and tissues predominantly expressed MPO. The blasts lacked expression of CD42b/CD61. Megakaryocytic differentiation might be stimulated by certain tissue factors. AML accompanying megakaryocytic differentiation in certain tissues and organs should be distinguished from acute megakaryoblastic leukemia. The mechanisms provoking acute coronary syndrome in acute myeloid leukemia are discussed.